A precoding aided space domain index modulation scheme for downlink multiuser MIMO systems - Souto, N. (2021)
In this correspondence, we propose a space domain index modulation (IM) scheme for the downlink of multiuser multiple-input multiple-output (MU-MIMO) systems. Instead of the most common approach where spatial bits select active receiver antennas, in the presented scheme the spatial information is mapped onto the transmitter side. This allows IM to better exploit large dimensional antenna settings which are typically easier to deploy at the base station. In order to mitigate inter-user interference and allow single user detection, a precoder is adopted at the BS. Furthermore, two alternative enhanced signal construction methods are proposed for minimizing the transmitted power or enable an implementation with a reduced number of RF chains. Simulation results for different scenarios show that the proposed approach can be an attractive alternative to conventional precoded MU-MIMO.